Caesarean Section Patterns Among PVTGs: A Comparative Analysis in Eastern India - Pradeep Kumar Panda; Rahul Sharma (Online Journal of Health & Allied Sciences)
Background: The rising global incidence of Caesarean section (CS) potentially reflects healthcare disparities between Particularly Vulnerable Tribal Groups (PVTG) and non-PVTG populations. This study analyzed CS patterns, indications, and outcomes between these groups at a district hospital in Gajapati, India. Methods: This prospective observational study examined 1,374 CS cases (177 PVTG and 1,197 non-PVTG) from October 2023 to October 2024. The analysis incorporated CS indications, APGAR scores, Robson classification, maternal age, and delivery timing using descriptive statistics and chi-square tests. Results: Previous CS emerged as the primary indication in both groups (PVTG, 29.9%; non-PVTG, 39.3%). PVTG women demonstrated higher rates of malpresentation (4.0% vs. 1.0%) and younger maternal age (23.2% vs. 19.3% for ages 18-20). Robson Group 5 predominated in non-PVTG cases (41.0% vs. 28.4%), while nocturnal CS rates were elevated among PVTG women (4.1% vs. 1.4%). Conclusions: The identified disparities necessitate targeted interventions, including enhanced antenatal care for young PVTG mothers, VBAC promotion among non-PVTG women, and improved round-the-clock obstetric services in the tribal regions.